1981
DOI: 10.1111/j.1755-3768.1981.tb06703.x
|View full text |Cite
|
Sign up to set email alerts
|

Disc Haemorrhage and Glaucoma

Abstract: The present material comprises 51 patients with at least one disc haemorrhage in at least one eye. A total of 127 hh were observed. The probability of finding a disc h increases with the number of examinations. The hypothesis that hh occur in all cases of glaucomatous destruction of the papillary tissue cannot be rejected, though not proven. H. seems to be connected with progression of field defects, though its effects are not immediately recognized. H. is detectable very early in the glaucomatous process; the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
29
1
3

Year Published

1981
1981
2012
2012

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 129 publications
(39 citation statements)
references
References 10 publications
6
29
1
3
Order By: Relevance
“…The occurence of manifest glaucoma in persons born before 1907, reported here, was consistent with those in persons born after 1906 (Bengtsson 1981a) and in persons with disc haemorrhages (Bengtsson et al 1981) reported elsewhere. Our collected results may be summarized as follows: the annual incidence of manifest glaucoma was 0.2% in women past 55 and men past 65.…”
Section: Discussionsupporting
confidence: 92%
“…The occurence of manifest glaucoma in persons born before 1907, reported here, was consistent with those in persons born after 1906 (Bengtsson 1981a) and in persons with disc haemorrhages (Bengtsson et al 1981) reported elsewhere. Our collected results may be summarized as follows: the annual incidence of manifest glaucoma was 0.2% in women past 55 and men past 65.…”
Section: Discussionsupporting
confidence: 92%
“…67 Furthermore, optic disc haemorrhages may represent areas of perivascular barrier dysfunction at the edge of the optic nerve head in glaucoma. 68 Potentially, breakdown of the blood-retinal barrier may alter the extracellular mileu and permit the extravasation of circulating peptides, such as the potent vasoconstrictor endothelin-1. 69 This may explain why patients with increased plasma levels of endothelin-1 are at greater risk of progression.…”
Section: Discussionmentioning
confidence: 99%
“…A number of population-based studies [1][2][3][4][5][6] have been published on the prevalence of disc haemorrhages (DHs), which reportedly precede both retinal nerve fibre loss and visual field damage in glaucoma. [7][8][9][10][11] In Japan, however, no population-based study has been carried out on the prevalence of DHs, although two groups of investigators 12,13 have reported the prevalence of DHs among large numbers of self-participating subjects in health-care programmes.…”
Section: Introductionmentioning
confidence: 99%